Allegra Lab: anthropology, law, art & world (Allegra Lab Association, 2016)
"Allegra Lab [...] is a collective of academics, an association and an online experiment founded in 2013. It explores creative ways to fill the ‘dead space’ that exists between traditional modes of academic publication and ongoing scholarly and societal debates. Allegra Lab discusses issues related to anthropology, law, art and beyond, and it is run by a diligent editorial team of professional scholars."
Gesehen am 20.05.2016
Keywords: Weblog